Study of capillary flow of nanofluids - Chew, Mei Ying. (2010)
The capillary flow of nanofluids into a horizontal capillary from a pendant droplet was investigated. Different fluid concentrations of titanium dioxide in a base fluid of glycerol - DI water with 4:1 ratio were used as the experimental fluids. The concentrations of titanium dioxide used were 1%, 0.5%, 0.1% and 0.05%. Capillaries of different sizes, including 300, 500 and 700 um, were used. The purpose was to compare the effects fluid viscosity and capillary size on capillary flow of nanofluids.